Study of Biomolecular Interactions of Mitochondrial Proteins Related to Alzheimer's Disease: Toward Multi-Interaction Biomolecular Processes - Hemmerová, Erika; Špringer, Tomáš; Krištofiková, Zdeňka; Homola, Jiří (Biomolecules, 2020)
Progressive mitochondrial dysfunction due to the accumulation of amyloid beta (Aβ) peptide within the mitochondrial matrix represents one of the key characteristics of Alzheimer's disease (AD) and appears already in its early stages. Inside the mitochondria, Aβ interacts with a number of biomolecules, including cyclophilin D (cypD) and 17β-hydroxysteroid dehydrogenase type 10 (17β-HSD10), and affects their physiological functions. However, despite intensive ongoing research, the exact mechanisms through which Aβ impairs mitochondrial functions remain to be explained. In this work, we studied the interactions of Aβ with cypD and 17β-HSD10 in vitro using the surface plasmon resonance (SPR) method and determined the kinetic parameters (association and dissociation rates) of these interactions. This is the first work which determines all these parameters under the same conditions, thus, enabling direct comparison of relative affinities of Aβ to its mitochondrial binding partners. Moreover, we used the determined characteristics of the individual interactions to simulate the concurrent interactions of Aβ with cypD and 17β-HSD10 in different model situations associated with the progression of AD. This study not only advances the understanding of Aβ-induced processes in mitochondria during AD, but it also provides a new perspective on research into complex multi-interaction biomolecular processes in general.
Keywords: biosenzitivní techniky; Alzheimer Disease; Surface Plasmon Resonance; Alzheimerova nemoc; 17-hydroxysteroidní dehydrogenasy; Humans; 17-Hydroxysteroid Dehydrogenases; lidé; peptidylprolylisomerasa F; amyloidní beta-protein; Peptidyl-Prolyl Isomerase F; povrchová plasmonová rezonance; Mitochondrial Proteins; Amyloid beta-Peptides; mitochondriální proteiny; Biosensing Techniques